2001
DOI: 10.1017/s0016756801004903
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic to Miocene K–Ar dates from eastern central Patagonian Cordillera plutons, Chile (45°–48° S)

Abstract: Thirty-nine K-Ar and one Ar-Ar radiometric dates from the eastern central MesoCenozoic Patagonian Batholith and eastern satellite plutons of the Aysén Region, of southern Chile between latitudes 45°and 48°S, combined with previous dating of seven plutons, have yielded six age groups: (1) Middle to Late Jurassic, (2) Early Cretaceous, (3) mid-Cretaceous, (4) Late Cretaceous, (5) Oligocene and (6) Miocene. In general, the Cretaceous and younger ages correspond to previous reported ages for other parts of the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 39 publications
2
61
0
1
Order By: Relevance
“…Very similar compositions were reported from the Cretaceous and Tertiary intrusions of the North Patagonian batholiths between 44 -478S (e.g. Pankhurst et al, 1999;Suárez and De La Cruz, 2001) and from the mid-Tertiary magmatism east of the Main Cordillera ( Fig. 5a; Muñoz et al, 2000).…”
Section: Sr-nd -Pb Isotopic Compositionsupporting
confidence: 77%
“…Very similar compositions were reported from the Cretaceous and Tertiary intrusions of the North Patagonian batholiths between 44 -478S (e.g. Pankhurst et al, 1999;Suárez and De La Cruz, 2001) and from the mid-Tertiary magmatism east of the Main Cordillera ( Fig. 5a; Muñoz et al, 2000).…”
Section: Sr-nd -Pb Isotopic Compositionsupporting
confidence: 77%
“…K-Ar, U-Pb and particularly Rb-Sr wholerock isochron data from plutonic rocks between ~41°S and 47°S reveal a systematic pattern with Jurassic to early Cretaceous intrusions at the eastern and western margins of the NPB, and Miocene ages towards the center (Hervé et al, 1979;Munizaga et al, 1988;Parada et al, 1987;Pankhurst et al, 1992Pankhurst et al, , 1999Suárez and De la Cruz, 2001). The episodic development of the NPB appears to be correlated with periods of increased convergence rates along the South American margin (Pankhurst et al, 1999).…”
Section: Geological Settingmentioning
confidence: 99%
“…It represents an important contractional tectonic episode that, according to the exposed evidences would have taken place during the Middle Jurassic. Intense deformation has been observed in the Toarcian beds of the Osta Arena Formation, deposited in the Chubut Basin and Recently, Rapela et al(2003) have indicated a southwestward migration of the magmatic arc from the Upper Triassic-early Lower Jurassic Central Patagonian Batholith to the Late Jurassic plutons located along the eastern side of the Patagonian Batholith (Suárez and De la Cruz, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…tectonic phase sometime during the intervening period. Also during the Middle Jurassic the Toarcian magmatic arc, that had a NNW orientation, ceased and the subsequent magmatic arc was emplaced further to the southwest (Rapela et al, 2003) and is identified in the Patagonian Cordillera, forming part of the Patagonian Batholith, with a north-south orientation, during the Late Jurassic (Suárez and De la Cruz, 2001). Hence, a major tectonism occurred during the Middle Jurassic with the closure of the Chubut Basin and the abrupt migration of the magmatic arc from a northeastern position to a southwestern location.…”
Section: Late Bajocian-callovian Contractional Tectonism In Western Cmentioning
confidence: 99%